(untitled) (Construction Economics and Building, 2019)
Life cycle carbon emissions (LCO2), made up of operational and embodied carbon, have become a major metric of building environmental performance and energy efficiency. Whilst there are now standard methods for operational carbon assessment due to its significance in LCO2, there is still less emphasis on embodied carbon counting. However, the relative contribution of embodied carbon is on the rise as buildings become increasingly energy efficient. Following the rule that only something which is measurable is manageable, it is essential that we are able to accurately count embodied carbon. This study therefore reviews the concept of LCO2 in buildings and further investigates the open source UK tools for embodied carbon counting. A comparative evaluation case study, which validates an earlier review, showed that there is no logic and consistency in the carbon figures produced by embodied carbon counting tools. This is mainly due to different system boundaries, varying underlying assumptions and methodological differences in calculation. The findings suggest that an industry-agreed data structure and common methodology is needed for embodied carbon counting. Generally, the study provides insights into the use and capabilities of the identified open source UK embodied carbon counting tools, and is relevant to the on-going debate about carbon regulation.